EFFECT OF MUCUNA (Mucuna pruriens) ON SPERMIOGRAMS OF WEST AFRICAN DWARF BUCKS - James Olamitibo Daramola (Tropical and Subtropical Agroecosystems, 2015)
The study was carried out to investigate the potential effect of Mucuna pruriens seed powder on spermiograms of West African Dwarf bucks (WAD). Twenty bucks were randomly assigned to five treatments consisting of four animals each receiving 0, 25, 50, 75, 100mg/Bw of Mucuna pruriens seed powder administered via oral route for 30 days consecutively. Following treatment, spermiograms of the animals were determined. The results showed that exposure of bucks to Mucuna pruriens powder led to a significant increase in weight gain, scrotal width, scrotal circumference, testicular weight, gonadosomatic index, sperm motility and testicular parenchyma of animals compared to the control and the improvement in these parameters was much pronounced in bucks that received 75mg Mucuna pruriens seed powder (P<0.05). Higher (P<0.05) sperm concentration was observed in 100mg inclusion of Mucuna pruriens seed powder compared to other treatments. The results showed a decline (P<0.05) in the level of testosterone with increasing level of Mucuna pruriens seed powder administration. The findings showed that oral administration of Mucuna pruriens seed powder to the bucks for 30 days resulted in improved testicular measurements and sperm quality without any adverse effect on structure of reproductive physiology of the bucks.